RETRACTED: LOGISTICAL APPROACHES TO IMPROVE THE MANAGEMENT OF PRODUCTION AND ECONOMIC ACTIVITIES OF BUSINESS ORGANIZATIONS - A. S. Senin; O. Yu. Mileshina (Модернизация, инновация, развитие)
Retracted articleThis article sets out the key aspects of the management of enterprise structures on the basis of logistizatsii, which allowed to establish a close relationship between the main processes (production), and provide processes (procurement, sales), ie introduce the implementation of these processes as a whole. The purpose / goal. The purpose of the work is to study the nature and characteristics of the organizational-economic mechanism of production and economic activity of enterprise structures on the basis of the logistical approach, identifying the problems and prospects of further development.Methodology. In this article we used a set of general scientific and special methods of investigation. General scientific research methods (analysis and synthesis) revealed a dynamic and structural specifics of the development of the global logistics market, to determine the future direction of development. Special investigation techniques (forecasting and modeling) have allowed to develop a set of recommendations aimed at increasing the level of innovation activity of logistic operators in line with global trends and immutable proposed changes in consumer demand in key market segments.Results. As part of the presentation of the present article the author has examined the nature, objectives and business structures control stages with the use of modern logistics approach.